The Adoption and Termination of Suppliers over the Business Cycle - Le Xu; Yang Yu; Francesco Zanetti (Center for Economic Studies and ifo Institute (CESifo), 2024)
We assemble a novel firm-level dataset to study the adoption and termination of suppliers over business cycles. We document that the aggregate number and rate of adoption of suppliers are procyclical. The rate of termination is acyclical at the aggregate level, and the cyclicality of termination encompasses large differences across producers. To account for these new facts, we develop a model with optimizing producers that incur separate costs for management, adoption, and termination of suppliers. These costs alter the incentives to scale up production and to replace existing with new suppliers. Both forces are critical to replicating the observed cyclicality in the adoption and termination rates at the producer and aggregate levels. Sufficiently high convexity in management relative to adjustment costs is required to replicate the observed decrease in the procyclicality of termination of suppliers with the size of producers. The optimal policy entails subsidies to management and adjustment costs.
Keywords: E32; L14; L24; 330; management and adjustment costs; adoption and termination of suppliers; business cycles